Colorless diamond and preparation method thereof
Through the high-temperature and high-pressure synthesis method of separately pressing the carbon source and catalyst, and alternately assembled with graphite sheets, catalyst sheets and nitrogen removal sheets, the problems of long synthesis time and low yield in the prior art are solved, and the efficient synthesis of high-grade colorless diamonds is achieved.
Patent Information
- Application Number
- CN202411795926.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-09
AI Technical Summary
It is difficult to synthesize high-grade colorless diamonds with high yields in the prior art, and the synthesis of temperature difference method has problems such as poor temperature stability, low yield and long production time.
The carbon source and the catalyst are separately pressed, and colorless diamonds are obtained by alternating assembly of graphite sheets, catalyst sheets and nitrogen removal sheets.
It improves the purity and color level of colorless diamonds, can reach D and E levels, shortens the synthesis time and improves the yield.
Smart Images

Figure CN119656978A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of diamond synthesis, in particular to a colorless diamond and a preparation method thereof. Background Art
[0002] The storage of natural diamonds is very limited, so many companies at home and abroad are currently cultivating colorless diamonds to fill the industry's needs and vacancies. Whether from the perspective of industrial demand or the demand of the jewelry industry, cultured diamonds are the best substitute for natural diamonds in the diamond industry, so the development prospects of the cultured diamond industry are very good. With the rapid development of domestic cultured diamond technology, the industry competition is becoming increasingly fierce, and the technology of artificial colorless diamonds is constantly improving and breaking through.
[0003] In the international standard diamond color grading system, the colors are divided into 23 grades according to the English letters DZ, and the colors decrease from DZ. Grade D is the highest grade, pure and colorless. At present, the main technology for cultivating artificial diamonds at home and abroad is still the temperature difference method. There are some disadvantages in synthesizing colorless diamonds by the temperature difference method. First, the suitable temperature range is too small, generally within 30℃, and the production stability is difficult to control; second, the yield is low, generally below 20ct, and the economic benefits are difficult to guarantee; third, the single block synthesis time is long, generally more than 24h. In addition, there are a few manufacturers who use the traditional method of synthesizing colorless diamonds by directly mixing catalysts, graphite, and crystal seeds and pressing the core column. This method has more limitations: first, it is difficult to synthesize high-grade large-particle colorless diamonds. Under the premise of ensuring quality, the main particle size can only reach about 1.0mm, and the color level of colorless diamonds is low, all below grade F; second, the uniformity of particle size and crystal shape is difficult to guarantee, and even a large proportion of connected crystals and shaped materials are prone to appear. Summary of the invention
[0004] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a colorless diamond and a preparation method and use thereof. The preparation method of colorless diamond described in the present application solves the problem that it is difficult to synthesize uniform high-quality colorless diamonds with high yield in the prior art.
[0005] To achieve the above objectives and other related objectives, the present invention is achieved through the following technical solutions.
[0006] The first aspect of the present invention discloses a method for preparing colorless diamond, the method comprising the following steps:
[0007] 1) Using seed crystals to seed the catalyst sheet;
[0008] 2) Alternately assembling a plurality of graphite sheets, denitrification sheets and the catalyst sheets after seeding, so that a denitrification sheet is contained between any of the graphite sheets and any of the catalyst sheets, to obtain a core column;
[0009] 3) coating the core column to obtain a synthetic block;
[0010] 4) Pressurizing and heating the synthetic block to obtain the colorless diamond.
[0011] Preferably, in step 1), the particle size of the seed crystal is 0.05-0.5 mm. For example, the particle size of the seed crystal can be 0.05-0.2 mm, 0.2-0.3 mm, 0.3-0.4 mm, or 0.4-0.5 mm.
[0012] Preferably, in step 1), the seed crystal is artificial diamond.
[0013] More preferably, the magnetic susceptibility of the seed crystal is less than 2*10 -5 SI. The magnetic susceptibility of the seed crystal can be 0.5*10 - 5 SI~0.8*10 -5 SI, 0.8*10 -5 SI~1*10 -5 SI, 1*10 -5 SI~1.3*10 -5 SI, 1.3*10 -5 SI~1.5*10 -5 SI, 1.5*10 -5 SI~1.8*10 -5 SI, 1.8*10 -5 SI~2*10 -5 SI.
[0014] More preferably, the crystal form of the artificial diamond is selected from one or more of hexahedron and hexa-octahedron.
[0015] Preferably, in step 1), the raw materials of the catalyst sheet include Fe powder and Ni powder. Based on the mass of the catalyst sheet, the content of the Fe powder is 30-80wt%, and the content of the Ni powder is 20-70wt%.
[0016] For example, the content of the Fe powder may be 30-40wt%, 40-50wt%, 50-60wt%, 60-65wt%, 65-70wt%, 70-75wt%, 75-80wt%.
[0017] For example, the content of Ni powder may be 20-25wt%, 25-28wt%, 28-30wt%, 30-40wt%, 40-50wt%, 50-60wt%, 60-65wt%, or 65-70wt%.
[0018] More preferably, the content of the Fe powder is 65-70wt%.
[0019] More preferably, the content of the Ni powder is 25-28wt%.
[0020] Preferably, the density of the catalyst sheet is 5.0-7.5 g / cm 3 .
[0021] For example, the density of the catalyst sheet can be 5.0 to 6.5 g / cm 3 , 6.5~6.7g / cm 3 , 6.7~6.88g / cm 3 , 6.88~6.9g / cm 3 , 6.9~6.92g / cm 3 , 6.92~6.94g / cm 3 , 6.94~7.2g / cm 3 7.2~7.5g / cm 3 .
[0022] More preferably, the density of the catalyst sheet is 6.5 to 6.94 g / cm 3 .
[0023] More preferably, the particle size of the Fe powder and the Ni powder is 300-500 mesh. For example, the particle size of the Fe powder and the Ni powder can be 300-350 mesh, 350-400 mesh, 400-450 mesh, or 450-500 mesh.
[0024] More preferably, the oxygen content of the Fe powder and the Ni powder is less than 200 ppm. For example, the oxygen content of the Fe powder and the Ni powder may be 50-100 ppm, 100-150 ppm, or 150-200 ppm.
[0025] More preferably, the raw materials of the catalyst sheet further include one or more of Co powder and Mn powder. Further, based on the mass of the catalyst sheet, the content of the Co powder is 1-10wt%, and the content of the Mn powder is 0.1-5wt%. Adding the Co powder and Mn powder can further improve the quality of the colorless diamond.
[0026] For example, the content of the Co powder may be 1-2wt%, 2-4wt%, 4-6wt%, 6-8wt%, or 8-10wt%.
[0027] For example, the content of the Mn powder may be 1-2wt%, 2-4wt%, 4-6wt%, 6-8wt%, or 8-10wt%.
[0028] Furthermore, the particle size of the Co powder and the Mn powder is 300-500 mesh. For example, the particle size of the Co powder and the Mn powder can be 300-350 mesh, 350-400 mesh, 400-450 mesh, or 450-500 mesh.
[0029] Furthermore, the oxygen content of the Co powder and the Mn powder is less than 200 ppm. For example, the oxygen content of the Co powder and the Mn powder may be 50-100 ppm, 100-150 ppm, or 150-200 ppm.
[0030] In actual operation, the thickness of the catalyst sheet can be adjusted arbitrarily according to the target colorless diamond particle size, as long as the colorless diamond growth space requirement is met. For example, if the target diamond particle size is 2.0 mm, the thickness of the catalyst sheet can be 6 mm.
[0031] In a preferred embodiment, the thickness of the catalyst sheet is 1-20 mm. For example, the thickness of the catalyst sheet can be 1-3 mm, 3-6 mm, 6-9 mm, 9-12 mm, 12-15 mm, 15-18 mm, or 18-20 mm.
[0032] In a more preferred embodiment, the thickness of the catalyst sheet is 1 to 13 mm.
[0033] Preferably, in step 2), the raw material of the graphite sheet is graphite powder, and the purity of the graphite powder is greater than or equal to 99.9%.
[0034] More preferably, the purity of the graphite powder is greater than or equal to 99.99%.
[0035] Preferably, the particle size of the graphite powder is 300-500 meshes. For example, the particle size of the graphite powder can be 300-350 meshes, 350-400 meshes, 400-450 meshes, or 450-500 meshes.
[0036] Preferably, the density of the graphite sheet is 1.5-2.0 g / cm 3 For example, the density of the graphite sheet can be 1.5 to 1.8 g / cm 3 1.8~1.85g / cm 3 1.85~1.88g / cm 3 1.88~1.9g / cm 3 1.9~1.91g / cm 3 1.91~1.93g / cm 3 1.93~1.95g / cm 3 1.95~2.0g / cm 3 .
[0037] More preferably, the density of the graphite sheet is 1.85 to 1.93 g / cm 3 .
[0038] In actual operation, the thickness of the graphite sheet can be adjusted arbitrarily according to the number of seed crystals and growth requirements, as long as it can support the growth of the seed crystals to the target colorless diamond particle size.
[0039] In a preferred embodiment, the thickness of the graphite sheet is 1 to 5 mm, such as 1.5 to 3.5 mm.
[0040] Preferably, in step 2), the nitrogen removal sheet is a metal sheet, and the metal includes one or more of Cu, Al, Ti, Zr, and Mg.
[0041] In actual operation, the thickness of the denitrification sheet can be adjusted arbitrarily according to the particle size and target quality of the target colorless diamond, as long as it can support the colorless diamond to reach the target grade. In a preferred embodiment, the thickness of the denitrification sheet is 0.05-0.5 mm. For example, the thickness of the denitrification sheet can be 0.05-0.1 mm, 0.1-0.15 mm, 0.15-0.2 mm, 0.2-0.3 mm, 0.3-0.4 mm, 0.4-0.5 mm.
[0042] In actual operation, the shapes and sizes of the graphite sheet, the catalyst sheet and the nitrogen removal sheet can be adjusted according to the actual colorless diamond output, preparation conditions and preparation equipment.
[0043] In a preferred embodiment, the cross-sections of the graphite sheet, the catalyst sheet and the denitrification sheet are all circular, and the diameters of the graphite sheet, the catalyst sheet and the denitrification sheet are 20 to 40 mm, such as 37 mm.
[0044] In a more preferred embodiment, the diameters of the graphite sheet, the catalyst sheet and the nitrogen removal sheet are consistent.
[0045] In actual operation, the preparation methods of the graphite sheet and the catalyst sheet can be arbitrarily selected as long as the density and component ratio requirements are met.
[0046] In a preferred embodiment, the graphite sheet and the catalyst sheet are prepared by pressing the raw materials into sheets, the pressing mold is a cemented carbide mold, and the pressing pressure is greater than or equal to 4t / cm 2 The pressing time is 3 to 5 seconds.
[0047] In a more preferred embodiment, the pressing mold is cylindrical, and the material of the pressing mold is tungsten carbide alloy.
[0048] In a more preferred embodiment, the preparation method of the catalyst sheet includes the following steps: mixing the raw materials uniformly and placing them in a granulator to obtain catalyst particles with a diameter of 1 to 3 mm; placing the catalyst particles in a mold and pressurizing them to obtain the catalyst sheet. For example, the diameter of the catalyst particles can be 1 to 1.5 mm, 1.5 to 2.0 mm, 2.0 to 2.5 mm, or 2.5 to 3 mm.
[0049] Preferably, in step 1), the step of seeding includes:
[0050] a1) preparing a cloth seed container, wherein a portion of the cloth seed container is a plane portion, a plurality of through holes are provided on the plane portion, and a sticky layer is attached to a side of the plane portion away from the feeding end;
[0051] a2) placing the seed crystal into the seed container, and shaking the seed container so that the seed crystal leaks out of the through hole and adheres to the adhesive layer;
[0052] a3) peeling the sticky layer with the seed crystal from the flat portion and overlapping it with the catalyst sheet, so that the side of the sticky layer with the seed crystal contacts the catalyst sheet, and applying pressure to the sticky layer and / or the catalyst sheet after overlapping, so that the seed crystal is completely pressed into the catalyst sheet.
[0053] More preferably, the aperture of the through hole is 0.05-0.5 mm. The aperture of the through hole is equal to the particle size of the seed crystal required for preparation, so that only one seed crystal required for preparation leaks out from any through hole.
[0054] For example, the diameter of the through hole may be 0.05-0.2 mm, 0.2-0.3 mm, 0.3-0.4 mm, or 0.4-0.5 mm.
[0055] More preferably, the feed end of the seeding container is detachably connected with a sealing cover, which prevents the seeds from spilling out of the feed part of the container during the seeding process.
[0056] More preferably, the sticky layer is a material with adhesive attached to the surface, and the material can be arbitrarily selected according to actual conditions, such as the material can be one or more of adhesive tape, paper, plastic and rubber.
[0057] More preferably, the thickness of the adhesive layer is less than or equal to 0.5 mm.
[0058] In actual operation, the material, shape and size of the seed container can be arbitrarily selected according to actual needs, as long as the shape and size of the plane portion and the adhesive layer are equal to those of the catalyst sheet. For example, the seed container can be made of metal and / or plastic.
[0059] In a preferred embodiment, the seed container is cylindrical, and the inner diameter of the seed container is consistent with the diameter of the catalyst sheet.
[0060] More preferably, in the step a2), the shaking time is 3 to 5 seconds, and the shaking is performed until each of the through holes is filled with the seed crystals.
[0061] More preferably, in the step a3), the peeling is performed manually, during which the human body does not come into contact with the seed crystals, and the seed crystals do not fall off the adhesive layer.
[0062] More preferably, before the alternating assembly, the seeding is repeated several times so that both sides of the catalyst sheet reach the required seeding density.
[0063] More preferably, in step a3), the applied pressure is 10-20 t / cm 2 The pressure is applied for 2 to 5 seconds.
[0064] Preferably, in the step 3), the coating process is to place the core column into a pyrophyllite block.
[0065] More preferably, before placing the core column into the pyrophyllite block, the core column is first placed into an insulating tube, then into a heating tube, and finally into the pyrophyllite block.
[0066] In a specific embodiment, the insulating tube is made of dolomite or magnesium oxide, with a thickness of 0.8-1.5 mm; the heating tube is made of iron or graphite, with a thickness of 0.2-0.5 mm. For example, the thickness of the insulating tube can be 0.8-1.0 mm, 1.0-1.2 mm, or 1.2-1.5 mm. For example, the thickness of the heating tube can be 0.2-0.25 mm, 0.25-0.35 mm, 0.35-0.45 mm, or 0.45-0.5 mm.
[0067] Preferably, the coating process further includes a step of removing impurities in the core column before the coating process.
[0068] Preferably, in step 4), the pressurization pressure is 5-6 Gpa. For example, the pressurization pressure may be 5-5.2 Gpa, 5.2-5.4 Gpa, 5.4-5.5 Gpa, 5.5-5.7 Gpa, 5.7-5.9 Gpa, or 5.9-6 Gpa.
[0069] Preferably, in step 4), the heating temperature is 1300-1400° C. For example, the heating temperature may be 1300-1320° C., 1320-1350° C., 1350-1380° C., or 1380-1400° C.
[0070] Preferably, in step 4), the pressurizing and heating time is 2 to 72 hours. For example, the pressurizing and heating time can be 2 to 7 hours, 7 to 15 hours, 15 to 25 hours, 25 to 35 hours, 35 to 45 hours, 45 to 55 hours, 55 to 65 hours, or 65 to 72 hours.
[0071] Preferably, after step 4), the step of extracting the colorless diamond is also included.
[0072] More preferably, the extraction method is selected from one or more of acid-base purification and / or electrolytic purification.
[0073] Preferably, the step 6) also includes a step of removing impurities in the core column.
[0074] More preferably, the device for removing impurities in the core column is a high-temperature vacuum furnace.
[0075] More preferably, the temperature for removing impurities from the core column is 1000-1100° C. For example, the temperature for removing impurities from the core column may be 1000-1020° C., 1020-1040° C., 1040-1060° C., 1060-1080° C., or 1080-1100° C.
[0076] More preferably, the time for removing impurities from the core column is 4 to 8 hours. For example, the time for removing impurities from the core column can be 4 to 5 hours, 5 to 6 hours, 6 to 7 hours, or 7 to 8 hours.
[0077] More preferably, the vacuum degree for removing impurities in the core column is 1*10 -1 As described above, the vacuum degree for removing impurities in the core column can be 1*10 -5 ~1*10 -4 , 1*10 -4 ~1*10 -3 , 1*10 -3 ~1*10 -2 , 1*10 -2 ~1*10 -1 .
[0078] In actual operation, the pressurizing and heating device can be arbitrarily selected according to operational or economic needs.
[0079] In a preferred embodiment, the pressurizing and heating device is a six-sided top press. The model of the six-sided top press can be arbitrarily selected according to the size of the specific core column, such as a six-sided top press of Φ560mm-Φ850mm.
[0080] In a more preferred embodiment, the six-sided top press has a model of Φ560mm.
[0081] The second aspect of the present application discloses a colorless diamond prepared by the preparation method as described above.
[0082] Preferably, the particle size of the colorless diamond is 0.3-5.0 mm. For example, the particle size of the colorless diamond can be 0.3-0.4 mm, 0.4-0.6 mm, 0.6-1.0 mm, 1.0-1.2 mm, 1.2-1.6 mm, 1.6-2.0 mm, 2.0-2.4 mm, 2.4-2.8 mm, 2.8-3.0 mm, 3.0-3.4 mm, 3.4-3.6 mm, 3.6-4.0 mm, 4.0-4.4 mm, 4.4-4.6 mm, 4.6-5.0 mm.
[0083] Preferably, the color of the colorless diamond is D or E grade.
[0084] Preferably, the colorless diamond has a hexa-octahedral crystal form.
[0085] In the present application, the quality detection of the colorless diamond refers to the detection method of "Diamond Grading GB / T 16554-2003".
[0086] Compared with the prior art, the present invention has the following beneficial effects:
[0087] 1) The present invention adopts a method of pressing the carbon source and the catalyst separately and assembling them alternately in sheets, and placing a nitrogen removal sheet in the middle of the two. Compared with the method of directly mixing and pressing the catalyst and graphite, the present invention can reduce the growth of spontaneous nuclei during the high temperature and high pressure synthesis process, and the synthesized colorless diamond has a higher purity and a significantly higher color level, which can reach D and E grades.
[0088] 2) The present invention designs the number and distribution of seed crystals according to the required particle size of colorless diamonds, and matches graphite sheets and catalyst sheets of appropriate thickness. While ensuring the grade and stability of colorless diamonds, the synthesis time is greatly shortened compared to the temperature difference method for synthesizing colorless diamonds, and the unit output is greatly improved. The content of colorless diamonds with a color of grade E or above is greater than 90wt%.
[0089] 3) Make a simple seeding container and adopt a simple and efficient seeding method. Compared with the traditional manual seeding method, it improves the seeding efficiency and reduces the probability of seed contamination. BRIEF DESCRIPTION OF THE DRAWINGS
[0090] Figure 1 Shown is a schematic longitudinal cross-sectional view of the core column described in the present application.
[0091] Figure 2 Shown is a schematic longitudinal cross-sectional view of the cloth seed container described in the present application.
[0092] Figure 3 Shown is a photograph of the colorless diamond described in Example 1 of the present application.
[0093] Figure 4 Shown is a photograph of the colorless diamond described in Example 2 of the present application.
[0094] Figure 5 Shown is a photograph of the colorless diamond described in Example 3 of the present application.
[0095] Figure 6 Shown is a photograph of the colorless diamond described in Example 4 of the present application.
[0096] Figure 7 Shown is a photograph of the colorless diamond described in Comparative Example 1 of the present application.
[0097] Description of Reference Numerals
[0098] 10 graphite sheet, 20 nitrogen removal sheet, 30 seed, 40 catalyst sheet, 50 seed container, 51 plane part, 52 sealing cover, 60 adhesive layer. DETAILED DESCRIPTION
[0099] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0100] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.
[0101] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both points of each numerical range and any value between the two points can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to implement the present invention.
[0102] In the present application, the applicant aims to solve the problem that it is difficult to synthesize high-grade colorless diamonds with high yield in the prior art. The applicant provides a method for preparing colorless diamonds. The colorless diamonds synthesized by the preparation method have high purity and can reach grade D and E. Compared with the synthesis of colorless diamonds by the temperature difference method, the synthesis time is greatly shortened and the unit yield is greatly improved.
[0103] like Figure 1 is a schematic diagram of a longitudinal section of the core column described in this application, such as Figure 1 As shown, the seed crystal 30 is embedded in the catalyst sheet 40 , and the nitrogen removal sheet 20 is disposed between the catalyst sheet 40 and the graphite sheet 10 .
[0104] It should be noted that the number of stacked layers of the denitrification sheet 20 , the catalyst sheet 40 and the graphite sheet 10 can be adjusted according to the target particle size of the synthesis and the size of the synthesis block.
[0105] It should be noted that the material, shape and size of the seed container 50 can be adjusted according to actual operation or economic needs.
[0106] In a Figure 2 In the specific embodiment shown, the seed container 50 is cylindrical, the inner diameter of the seed container 50 is 20-40 mm, and the height is 10-30 mm; a plurality of through holes are evenly arranged on the plane portion 51 of the seed container 50, and the seed container 50 also includes a sealing cover 52, and the sealing cover 52 prevents the crystal seeds from spilling during seeding. In actual operation, the aperture of the through hole is consistent with the particle size of the crystal seed, such as the aperture of the through hole is 0.05-0.5 mm; the number of the through holes can be adjusted according to the seed density requirements.
[0107] In a Figure 2 In the specific embodiment shown, the adhesive layer 60 is adhered to the side of the plane portion 51 away from the feed port. The shape and size of the adhesive layer are consistent with the plane portion 51. The thickness of the adhesive layer 60 is less than or equal to 0.5 mm.
[0108] In actual operation, the shape, size and material of the pressing die described in this application can be arbitrarily selected according to actual needs. In the following specific embodiment, the material of the pressing die is tungsten carbide hard alloy, the pressing die is cylindrical, the inner diameter of the pressing die is 37mm, and the height is 30mm.
[0109] In the following specific embodiments, the difference between the cloth seed containers in each embodiment is only the diameter and number of the through holes. The cloth seed containers 50 are all cylindrical, and the inner diameter of the cloth seed containers 50 is 37 mm, and the height is 30 mm; the diameters of the through holes are 0.05 mm, 0.2 mm, and 0.5 mm respectively; the cloth seed container 50 also includes a sealing cover 52, and the side of the plane portion 51 away from the feed port is pasted with the adhesive layer 60, which is a round adhesive tape with a diameter of 37 mm and a thickness of 0.1 mm.
[0110] In the following embodiments of the present application, the finished product refers to colorless diamonds with a color of grade D and grade E, and the yield rate is calculated as the mass ratio of colorless diamonds with a color of grade D and grade E to the total colorless diamonds.
[0111] Example 1
[0112] This embodiment provides a method for preparing colorless diamond, the preparation method comprising the following steps:
[0113] 1) Pressing graphite sheet 10: Add high-purity graphite powder into the above pressing mold, use a four-column press, set parameters, and press at 5t / cm 2 The high-purity graphite powder was pressed in a mold for 3 seconds under a pressure of , and a graphite sheet 10 was obtained by pressing. The above steps were repeated 5 times to obtain 5 sheets with a thickness of 3 mm, a diameter of 37 mm, and a density of 1.9 g / cm 3 The graphite sheet 10, the purity of the high-purity graphite powder is greater than or equal to 99.99%, and the particle size of the high-purity graphite powder is 300 mesh;
[0114] 2) Pressing the catalyst sheet 40: Fe powder, Ni powder, Co powder and Mn powder are mixed to obtain catalyst powder, wherein the particle size of the Fe powder, Ni powder, Co powder and Mn powder is 300 mesh, and the oxygen content of the Fe powder, Ni powder, Co powder and Mn powder is 100ppm. Based on the total mass of the catalyst powder, the content of Fe powder is 70wt%, the content of Ni powder is 25wt%, the content of Co powder is 4wt% and the content of Mn powder is 1wt%; the mixing is carried out by a three-dimensional mixer, the speed of the mixing is 15r / min, and the time is 5h to obtain the catalyst powder, and then the catalyst powder is placed in a granulator to granulate into catalyst particles with a diameter of 2.5mm, and finally the catalyst particles are pressed into catalyst sheets, and the steps of pressing the catalyst sheet include: adding the catalyst particles into the above-mentioned pressing mold, using a four-column press, setting parameters, and pressing at 8t / cm 2 The catalyst particles were pressed in a mold for 5 seconds under a pressure of , and a catalyst sheet 40 was obtained. The above steps were repeated 4 times to obtain 4 sheets with a thickness of 6 mm, a diameter of 37 mm, and a density of 6.9 g / cm 3 Catalyst sheet 40.
[0115] 3) placing the seed crystal 30 in the seed container 50, wherein the through hole diameter of the seed container is 0.2 mm and the number of through holes is 114, and shaking the seed container 50 to make the seed crystal 30 leak out from the through hole and evenly adhere to the adhesive layer 60;
[0116] The viscous layer 60 uniformly stained with the seed crystal 30 is gently removed from the seed container 50 and attached to the catalyst sheet 40; a four-column press is used at 10t / cm 2 Under pressure, the seed crystal 30 is evenly and completely pressed into the catalyst sheet 40, and then the sticky layer 60 is gently removed to complete the seeding. The seed crystal 30 is artificial diamond with a particle size of 0.2 mm, a hexahedral crystal form, and a magnetic susceptibility of 1.0*10 -5 SI.
[0117] 4) Repeat step 3) to plant crystal seeds on both sides of all catalyst sheets 40;
[0118] 5) Assembling the core column: Alternately assemble the graphite sheet 10, the catalyst sheet 40 after seeding and the nitrogen removal sheet 20 to obtain the following Figure 1 The core column shown; based on the total mass of the denitrification sheet 20, the Ti content of the denitrification sheet 20 is 80wt%, the Al content is 20wt%, and the thickness of the denitrification sheet 20 is 0.2mm;
[0119] 6) The core column is placed in a high temperature vacuum furnace for 6 hours, the temperature is set to 1000°C, and the vacuum degree is 1×10 -3 , remove impurities, vacuum pack after being taken out of the oven for later use;
[0120] 7) The vacuum-treated core column is placed in an insulating tube that matches it, and then placed in a heating tube that matches the insulating tube, and finally placed in a pyrophyllite block to obtain a synthetic block. The insulating tube is made of dolomite with a thickness of 1.0 mm; the heating tube is made of iron with a thickness of 0.25 mm.
[0121] 8) The synthetic block is placed in a Φ560mm six-sided top press for synthesis. By setting the process curve, the pressure required for synthesis is 6.0GPa and the temperature is 1350℃. The power curve control is set as follows: the starting power is 6800W, maintained for 550s, then the power is reduced to 6500W within 25s, maintained for 100s, and then the power is slowly reduced to 6300W within 23h, and maintained for 80s, and finally naturally cooled. The pressure curve control is set as follows: the above-mentioned six-sided top press is pressurized from 0MPa to 55MPa at a speed greater than 2MPa / s and starts heating, stops pressurizing, maintains for 450s, and then continues pressurizing, and pressurizes to 70MPa within 20s, stops pressurizing, maintains for 20s, increases the pressure to 74MPa within 23h, maintains for 15s, and finally naturally releases the pressure.
[0122] 9) Purification to obtain the colorless diamond: The purification comprises the following steps: crushing the synthetic block into particles of 5-10 mm by a four-column press, and then placing the particles in an electrolytic cell with a hydrochloric acid system as an electrolytic mother liquid for electrolysis, the electrolysis time is 50-100 hours, and the electrolysis voltage is 6V to 12V DC voltage to obtain a diamond mixture; mixing nitric acid and sulfuric acid in proportion, adding them to the diamond mixture to completely immerse the diamond mixture, and then heating to 280°C for 2-10 hours to obtain a treated diamond mixture; adding sodium hydroxide to the treated diamond mixture in a ratio of 1:5, mixing thoroughly, heating the mixture to react, and keeping it in a molten state for 1-5 hours, then pouring out the liquid; soaking the diamond again in nitric acid to neutralize it to neutrality, pouring out the liquid, and drying the diamond at 150°C.
[0123] The colorless diamond obtained in this embodiment is obtained through testing:
[0124] 1) Figure 3 It was taken by the RX-A4K measurable camera of Ruixian Optical Instrument Co., Ltd. Figure 3 As shown, the crystal form of the colorless diamond is hexahedron;
[0125] 2) The colorless diamond is sieved by using an ES-04 electromagnetic vibrating sieve machine produced by Shenzhen Ruichengjie Technology Co., Ltd. The main particle size of the colorless diamond is 7-10 mesh.
[0126] 3) According to the test of "Diamond Grading GB / T 16554-2003", the color of the colorless diamond can reach grade D and grade E;
[0127] 4) The yield of the colorless diamond in a single synthetic block is 69.5 ct;
[0128] 5) The yield rate of the colorless diamond is 91.2%.
[0129] Example 2
[0130] The difference from Example 1 is that in this embodiment, based on the total mass of the catalyst powder, the content of Fe powder is 65wt%, the content of Ni powder is 30wt%, the content of Co powder is 4wt% and the content of Mn powder is 1wt%; 9 pieces with a thickness of 1.8mm, a diameter of 37mm and a density of 1.85g / cm 3 Graphite sheets; 8 sheets with a thickness of 3.0 mm, a diameter of 37 mm, and a density of 6.5 g / cm 3 catalyst sheet; the thickness of the nitrogen removal sheet is 0.1 mm; the seed particle size is 0.05 mm; the through hole diameter of the seed container is 0.05 mm, and the number of through holes is 252.
[0131] In the step 8), the synthetic block is placed in a Φ560mm six-sided top press for synthesis, and the pressure required for synthesis is 6.0GPa and the temperature is 1300°C by setting the process curve. The power curve control is set as follows: the starting power is 6600W, maintained for 550s, and then the power is reduced to 6300W within 25s, maintained for 100s, and then the power is slowly reduced to 6200W within 12h, and maintained for 80s, and finally naturally cooled. The pressure curve control is set as follows: the six-sided top press is pressurized from 0MPa to 55MPa at a speed greater than 2MPa / s and heated, the pressurization is stopped, and the pressurization is continued after 450s, and the pressure is pressurized to 71MPa within 15s, the pressurization is stopped, and maintained for 20s, and the pressure is increased to 75.5MPa within 12h and maintained for 20s, and finally the pressure is naturally released.
[0132] The colorless diamond obtained in this embodiment is obtained through testing:
[0133] 1) Figure 4 It was taken by the RX-A4K measurable camera of Ruixian Optical Instrument Co., Ltd. Figure 4 As shown, the crystal form of the colorless diamond is hexahedron;
[0134] 2) using the ES-04 electromagnetic vibrating screen machine of Shenzhen Ruichengjie Technology Co., Ltd. to screen and obtain the main particle size of the colorless diamond to be 14-16 mesh;
[0135] 3) According to the test of "Diamond Grading GB / T 16554-2003", the color of the colorless diamond can reach grade D and grade E;
[0136] 4) The single piece yield of the colorless diamond is 84.3 ct.
[0137] 5) The yield rate of the colorless diamond is 90.7%.
[0138] Example 3
[0139] The difference from Example 1 is that in this embodiment, based on the total mass of the catalyst powder, the content of Fe powder is 70wt%, the content of Ni powder is 28wt%, and the content of Co powder is 2wt%; 4 pieces with a thickness of 3.0mm, a diameter of 37mm, and a density of 1.91g / cm 3 Graphite sheets, 3 sheets with a thickness of 9.0 mm, a diameter of 37 mm, and a density of 6.92 g / cm 3 The catalyst sheet is 0.15 mm thick. The diameter of the through hole of the seed container is 0.2 mm, and the number of through holes is 52.
[0140] In the step 8), the synthetic block is placed in a Φ560mm six-sided top press for synthesis, and the pressure required for synthesis is 5.5GPa and the temperature is 1400°C by setting the process curve. The power curve control is set as follows: the starting power is 6900W, maintained for 550s, and then the power is reduced to 6650W within 25s, maintained for 100s, and then the power is slowly reduced to 6400W within 47.5h, and maintained for 80s, and finally naturally cooled. The pressure curve control is set as follows: the six-sided top press is pressurized from 0MPa to 55MPa at a speed greater than 2MPa / s and heated, the pressurization is stopped, the pressurization is continued after 450s, and the pressure is pressurized to 70.5MPa within 15s, the pressurization is stopped, maintained for 20s, the pressure is increased to 74.5MPa within 47.5h, maintained for 15s, and finally naturally released.
[0141] The colorless diamond obtained in this embodiment is obtained through testing:
[0142] 1) Figure 5 It was taken by the RX-A4K measurable camera of Ruixian Optical Instrument Co., Ltd. Figure 5 As shown, the crystal form of the colorless diamond is hexahedron;
[0143] 2) The colorless diamond is sieved by using the ES-04 electromagnetic vibrating sieve machine of Shenzhen Ruichengjie Technology Co., Ltd., and the main particle size of the colorless diamond is 5-6 mesh;
[0144] 3) According to the test of "Diamond Grading GB / T 16554-2003", the color of the colorless diamond can reach grade D and grade E;
[0145] 4) The single piece yield of the colorless diamond is 50.6 ct.
[0146] 5) The yield rate of the colorless diamond is 90.3%.
[0147] Example 4
[0148] The difference from Example 1 is that 16 tablets with a thickness of 1.5 mm, a diameter of 37 mm, and a density of 1.93 g / cm 3 Graphite sheets, 15 sheets with a thickness of 1.0 mm, a diameter of 37 mm, and a density of 6.88 g / cm 3 catalyst sheet; the thickness of the nitrogen removal sheet is 0.05 mm; the seed particle size is 0.05 mm; the through hole diameter of the seed container is 0.05 mm, and the number of through holes is 1220.
[0149] The synthetic block is placed in a Φ560mm six-sided top press for synthesis. By setting the process curve, the pressure required for synthesis is 5.2GPa and the temperature is 1300℃. The power curve control is set as follows: the starting power is 6500W, maintained for 550s, then the power is reduced to 6300W within 25s, maintained for 50s, and then the power is slowly reduced to 6200W within 2h, and maintained for 100s, and finally naturally cooled. The pressure curve control is set as follows: the above-mentioned six-sided top press is pressurized from 0MPa to 55MPa at a speed greater than 2MPa / s and starts heating, stops pressurizing, maintains for 400s, and then continues pressurizing, and pressurizes to 70MPa within 10s, stops pressurizing, maintains for 20s, increases the pressure to 73MPa within 2h, maintains for 15s, and finally naturally releases the pressure.
[0150] The colorless diamond obtained in this embodiment is obtained through testing:
[0151] 1) Figure 6 It was taken by the RX-A4K measurable camera of Ruixian Optical Instrument Co., Ltd. Figure 6 As shown, the crystal form of the colorless diamond is hexahedron;
[0152] 2) using the ES-04 electromagnetic vibrating screen machine of Shenzhen Ruichengjie Technology Co., Ltd. to screen and obtain the main particle size of the colorless diamond to be 40-45 mesh;
[0153] 3) According to the test of "Diamond Grading GB / T 16554-2003", the color of the colorless diamond can reach grade D;
[0154] 4) The single piece yield of the colorless diamond is 98.4 ct.
[0155] 5) The yield rate of the colorless diamond is 92.5%;
[0156] Example 5
[0157] The difference from Example 1 is that in this embodiment, based on the total mass of the denitrification sheet, the content of Ti in the denitrification sheet is 80wt%, the content of Al is 10wt%, and the content of Zr is 10wt%; 3 sheets with a thickness of 3.5mm, a diameter of 37mm, and a density of 1.88g / cm 3 Graphite sheets, 2 sheets with a thickness of 13.0 mm, a diameter of 37 mm, and a density of 6.94 g / cm 3 catalyst sheet; the thickness of the nitrogen removal sheet is 0.5 mm; the seed particle size is 0.5 mm; the through hole diameter of the seed container is 0.5 mm, and the number of through holes is 24.
[0158] The synthetic block is placed in a Φ560mm six-sided top press for synthesis. By setting the process curve, the pressure required for synthesis is 5.0GPa and the temperature is 1300℃. The power curve control is set as follows: the starting power is 6400W, maintained for 1000s, then the power is reduced to 6300W within 100s, maintained for 50s, and then the power is slowly reduced to 6200W within 70h, and maintained for 300s, and finally naturally cooled. The pressure curve control is set as follows: the above-mentioned six-sided top press is pressurized from 0MPa to 55MPa at a speed greater than 2MPa / s and starts heating, stops pressurizing, maintains for 1000s, and then continues pressurizing, and pressurizes to 70MPa within 10s, stops pressurizing, maintains for 20s, increases the pressure to 73.5MPa within 70h and maintains for 300s, and finally naturally releases the pressure.
[0159] The colorless diamond obtained in this embodiment is obtained through testing:
[0160] 1) The colorless diamond was photographed by a measurable camera RX-A4K of Ruixian Optical Instrument Co., Ltd. The crystal form of the colorless diamond is hexahedral;
[0161] 2) using the ES-04 electromagnetic vibrating screen machine of Shenzhen Ruichengjie Technology Co., Ltd. to screen and obtain the main particle size of the colorless diamond to be 4-5 mesh;
[0162] 3) According to the test of "Diamond Grading GB / T 16554-2003", the color of the colorless diamond can reach grade D and grade E;
[0163] 4) The single piece yield of the colorless diamond is 50.2 ct.
[0164] 5) The yield rate of the colorless diamond is 90%;
[0165] Comparative Example 1
[0166] The difference from Example 1 is that, in this comparative example, the catalyst powder, the high-purity graphite powder and the metal powder corresponding to the nitrogen removal sheet are mixed for 5 hours using a TD-9 three-dimensional mixer at 15 r / min according to the amounts in Example 1, and then the mixed powder is placed in a YC-100BX4 granulator to granulate into mixed particles with a diameter of 3.0 mm, and the seed crystals are buried therein, and finally, the particles are pressed into core columns, and then the operations of steps 6) to 9) described in Example 1 are performed to obtain colorless diamond.
[0167] The colorless diamond obtained in this embodiment is obtained through testing:
[0168] 1) If Figure 7 As shown, it is observed that there are many internal impurities in the colorless diamond;
[0169] 2) According to the test of "Diamond Grading GB / T 16554-2003", the color of the colorless diamond is yellowish black, which does not meet the grading standards;
[0170] 3) The yield rate of the colorless diamond is 0;
[0171] 4) The output of the colorless diamond is 78.4 ct.
[0172] Comparative Example 2
[0173] This comparative example provides a method for preparing colorless diamond using a temperature difference method. The temperature difference method used in this comparative example includes the following steps:
[0174] 1) Seeding: 114 crystal seeds are evenly distributed and pressed on the crystal bed. The crystal seeds are consistent with those in Example 1. The crystal bed has a thickness of 2 mm, a diameter of 37 mm, and is made of magnesium oxide.
[0175] 2) Assembling the core column: Assemble the dolomite core, graphite sheet, catalyst sheet, denitrification sheet and crystal bed sheet with seeded crystals in sequence to obtain a core column. The dolomite core has a thickness of 15 mm and a diameter of 37 mm. The graphite sheet, catalyst sheet and denitrification sheet in this comparative example are the same as those in Example 1.
[0176] 3) The core column is placed in a high temperature vacuum furnace for 6 hours, the temperature is set to 1000°C, and the vacuum degree is 1×10 -3 , remove impurities, vacuum pack after being taken out of the oven for later use;
[0177] 4) Put the vacuum-treated core column into an insulating tube that matches it, then into a heating tube that matches the insulating tube, and finally into a pyrophyllite block to obtain a synthetic block. The insulating tube is made of dolomite and has a thickness of 1.0 mm;
[0178] The heating tube is made of iron and has a thickness of 0.25 mm.
[0179] 5) The synthetic block is placed in a Φ560mm six-sided top press for synthesis. By setting the process curve, the pressure required for synthesis is 5.5GPa and the temperature is 1200℃. The power curve control is set as follows: the starting power is 6000W, maintained for 1000s, then the power is reduced to 5900W within 25s, maintained for 100s, and then the power is slowly reduced to 5700W within 47h, and maintained for 80s, and finally naturally cooled. The pressure curve control is set as follows: the above-mentioned six-sided top press is pressurized from 0MPa to 50MPa at a speed greater than 2MPa / s and starts heating, stops pressurizing, maintains for 1100s, and then continues pressurizing, and pressurizes to 65MPa within 20s, stops pressurizing, maintains for 20s, increases the pressure to 70MPa within 47h, maintains for 10s, and finally naturally releases the pressure.
[0180] 6) Purification, the specific steps are the same as step 9) described in Example 1.
[0181] The colorless diamond obtained in this embodiment is obtained through testing:
[0182] 1) The colorless diamond is obtained by taking a photo with the RX-A4K measurable camera of Ruixian Optical Instrument Co., Ltd. The crystal form of the colorless diamond is hexahedral;
[0183] 2) The colorless diamond is sieved by using an ES-04 electromagnetic vibrating sieve machine produced by Shenzhen Ruichengjie Technology Co., Ltd. The main particle size of the colorless diamond is 8-12 mesh.
[0184] 3) According to the test of "Diamond Grading GB / T 16554-2003", the color of the colorless diamond can reach grade D and grade E;
[0185] 4) The yield of the colorless diamond in a single synthetic block is 10.2 ct.
[0186] 5) The yield rate of the colorless diamond is 90.5%.
[0187] In summary, the method for preparing colorless diamond described in the present invention adopts a method of separately pressing a carbon source and a catalyst, and assembling them alternately in sheets, and placing a nitrogen removal sheet in the middle of the two, so that the growth of spontaneous nuclei can be reduced during the high temperature and high pressure synthesis process of colorless diamond, and the synthesized colorless diamond has a high purity and a significantly high color grade, which can reach grade D and grade E. Compared with the temperature difference method for synthesizing colorless diamond, the synthesis time is greatly shortened and the unit output is greatly improved.
[0188] The present invention effectively overcomes various shortcomings of the prior art and has high industrial utilization value.
[0189] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing colorless diamond, characterized in that: The preparation method comprises the following steps: 1) Using seed crystals to seed the catalyst sheet; 2) Alternately assembling a plurality of graphite sheets, denitrification sheets and the catalyst sheets after seeding, so that a denitrification sheet is contained between any of the graphite sheets and any of the catalyst sheets, to obtain a core column; 3) coating the core column to obtain a synthetic block; 4) Pressurizing and heating the synthetic block to obtain the colorless diamond.
2. The preparation method according to claim 1, characterized in that: In the step 1), the seed crystal has a particle size of 0.05 to 0.5 mm; And / or, in step 1), the seed crystal is artificial diamond; And / or, in the step 1), the raw materials of the catalyst sheet include Fe powder and Ni powder, and based on the mass of the catalyst sheet, the content of the Fe powder is 30-80wt%, and the content of the Ni powder is 20-70wt%; And / or, the density of the catalyst sheet is 5.0-7.5 g / cm 3 ; And / or, in step 2), the raw material of the graphite sheet is graphite powder, and the purity of the graphite powder is greater than or equal to 99.9%, The particle size of the graphite powder is 300-500 mesh; And / or, the density of the graphite sheet is 1.5-2.0 g / cm 3 ; And / or, in step 2), the nitrogen removal sheet is a metal sheet, and the metal includes one or more of Cu, Al, Ti, Zr, and Mg; And / or, the thickness of the nitrogen removal sheet is 0.05-0.5 mm.
3. The preparation method according to claim 2, characterized in that: The crystal form of the artificial diamond is selected from one or more of hexahedron and hexa-octahedron; And / or, the particle size of the Fe powder and the Ni powder is 300-500 mesh; and / or, the oxygen content of the Fe powder and the Ni powder is less than 200 ppm; And / or, the raw material of the catalyst sheet further comprises one or more of Co powder and Mn powder, and based on the mass of the catalyst sheet, the content of the Co powder is 1-10wt%, and the content of the Mn powder is 0.1-5wt%.
4. The preparation method according to claim 3, characterized in that: The particle size of the Co powder and the Mn powder is 300-500 mesh; And / or, the oxygen content of the Co powder and the Mn powder is less than 200 ppm.
5. The preparation method according to claim 1, characterized in that: In the step 1), the step of planting the seeds includes: a1) preparing a cloth seed container, wherein one end of the cloth seed container is a plane portion, the plane portion is provided with a plurality of through holes, and a sticky layer is pasted on a side of the plane portion away from the feeding end; a2) placing the seed crystal into the seed container, and shaking the seed container so that the seed crystal leaks out of the through hole and adheres to the adhesive layer; a3) peeling the sticky layer with the seed crystal from the flat portion and overlapping it with the catalyst sheet, so that the side of the sticky layer with the seed crystal contacts the catalyst sheet, and applying pressure to the sticky layer and / or the catalyst sheet after overlapping, so that the seed crystal is completely pressed into the catalyst sheet.
6. The preparation method according to claim 5, characterized in that: The aperture of the through hole is 0.05 to 0.5 mm; And / or, a detachable sealing cover is connected to the feeding end of the cloth seed container.
7. The preparation method according to claim 1, characterized in that: In the step 3), the coating process is to place the core column into a pyrophyllite block; And / or, the coating process further includes a step of removing impurities in the core column; And / or, in the step 4), the pressurization pressure is 5 to 6 GPa; And / or, in the step 4), the heating temperature is 1300-1400° C.; And / or, in the step 4), the time of pressurizing and heating is 2 to 72 hours; And / or, after step 4), the method further includes a step of extracting the colorless diamond.
8. The preparation method according to claim 7, characterized in that: The temperature for removing impurities in the core column is 1000-1100° C.; And / or, the time for removing impurities in the core column is 4 to 8 hours; And / or, the vacuum degree for removing impurities in the core column is 1*10 -1 above; And / or, the extraction method is selected from one or more of acid-base purification and / or electrolytic purification.
9. A colorless diamond prepared by the preparation method according to any one of claims 1 to 8.
10. The colorless diamond according to claim 9, characterized in that The particle size of the colorless diamond is 0.3-5.0 mm; And / or, the color of the colorless diamond is grade D or grade E; And / or, the colorless diamond has a hexa-octahedral crystal form.
Citation Information
Patent Citations
Synthesis block and synthesis method of colorless diamonds for artificially synthesized jewelries
CN106215808A
Seed crystal distribution method for synthesizing colorless diamond by powder catalyst constant-temperature method
CN115337866A
Artificial synthesis method of colorless diamond
CN117899750A
Cavity device for synthesizing colorless diamond large single crystals by using double graphite electrodes
CN221797728U
Boron doped synthetic diamond material
GB201905049D0
Cited By
Colorless diamond and preparation method therefor
WO2026123536A1